METHODS OF SUPERVISING THE TECHNICAL AND TACTICAL TRAINING OF QUALIFIED BASKETBALL PLAYERS - Dadabayev R. R. (Web of Journals Publishing, 2024)
The modern level of basketball development, speed is closely related to the manifestation of technical tactics and Agile involves making many changes to the process of improving methods.
Keywords: Modern basketball, top category, technique and tactics, pedagogical observation, to the basket the ball throw _ promptness and agility methods , sprinter running.